Prevalence and Factors of Anxiety During the Coronavirus-2019 Pandemic Among Teachers in Saudi Arabia - Alhazmi, Riyadh A.; Alghadeer, Sultan; Al-Arifi, Mohamed N.; Alamer, Asma A.; Mubarak, Abdullah M.; Alwhaibi, Abdulrahman; Alfayez, Raghad; Alsubaie, Sara (Frontiers in Public Health, 2022)
Background: Teachers play a central role in successful education. Due to the COVID-19 pandemic, regular in-person attendance in classes at all levels of education has been disrupted for more than one year in many countries. These lockdowns, which include the discontinuation of in person learning at schools and universities has presented a significant challenge for teachers to adapt to online teaching. Given this rapid format change, occupational anxiety levels among educators has increased. Objective: The primary objective of this study was to assess the prevalence of anxiety among teachers in Saudi Arabia. A secondary objective was to explore characteristics of teachers associated with the level of anxiety level during the period of lockdown. Methods: An anonymous, online cross-sectional study was carried for three months (February 2021 through April 2021). The questionnaire consisted of four sections and included the Generalized Anxiety Disorder instrument (GAD-7). Chi-square tests were completed for categorical comparisons while binary logistic regressions were used for associative relationship exploration. The IRB at King Saudi University Medical City, Saudi Arabia approved this study. Results: A total of 742 respondents completed the survey yielding an anxiety prevalence of 58.2 % among teachers. Medium degree of statistically significant differences identified as marital status (p = 0.046). women had higher anxiety (65.3%) than men (34.7%) but gender with anxiety was low degree of statistical significance compared with non-anxiety status (p=0.697). The odds of anxiety among middle teachers was twice (OR = 2.01) as high as the odds of anxiety among other levels of teacher (p = 0.01, 95% CI 0.94-4.26). Conclusions: This study identified that many teachers experienced anxiety during the lockdown, especially women and middle school teachers. Future studies should identify contributing factors to estimate the magnitude of the exposure to anxiety between different types of teachers to help establish better preventive measures based on the workplace environment.